Henryana magnifica Yoshimoto (Hymenoptera: Eulophidae) in Brazil: New Records for the Amazon Rainforest and Brazilian Dry Forest - Daniell Rodrigo Rodrigues Fernandes; Karine Schoeninger; Rogéria Inês Rosa Lara; Nelson Wanderley Perioto (EntomoBrasilis, 2014)
Henryana magnifica Yoshimoto (Hymenoptera: Eulophidae) is reported for the first time in an Amazon rainforest area of Amazonas State and in a Brazilian Dry Forest area of Rio Grande do Norte State, Brazil.